Adaptive Logistics Management and Optimization through Artificial Intelligence - Micieta, Branislav; Staszewska, Jolanta; Binasova, Vladimira; Hercko, Jozef (Communications - Scientific letters of the University of Zilina, 2017)
Adaptive logistics management can be reached using artificial intelligence and optimization processes. The paper deals with adaptive logistics management in order to allow direct communication between logistics management systems and logistics facilities, machines, robots and mobile robot system using AI and adaptive behavior in logistics processes. In addition, the paper discusses development trends in adaptive logistics processes and new features such as holonic systems of autonomic logistics management.